Study on the kinetics of gas-solid based synergistic reduction of limonite carbon-containing pellets - gao, guofeng; zhou, xiaolei; zhe, shi; liu, lanpeng (Journal of Mining and Metallurgy, Section B: Metallurgy, 2021)
The gas-solid base synergistic reduction of pellets is an innovative and effective method for iron ore smelting. With the development and utilization of iron resources, the reserves of rich mines have been greatly reduced. Therefore, as a typical lean ore resource, the comprehensive utilization of limonite has become increasingly important. In order to further study the reduction kinetics of pellets, this study used coke and reducing gases (CO and H2) as reducing agents to study the reduction characteristics and changes of limonite carbon-containing pellets. The research results show that the degree of reduction of pellets gradually increases with increasing temperature. The C/O molar ratio has a greater influence on the reduction degree of pellets in the N2 atmosphere, but does not have a significant effect in the CO and H2 atmospheres. And the maximum reduction rate increases with increasing temperature. The reduction reaction is most difficult to proceed in the N2 atmosphere, and the reaction is most likely to occur in the CO atmosphere. The microscopic analysis of pellets using EPMA and XRD found that the pellets reduced in N2 atmosphere had the smallest porosity and the pellets reduced in H2 atmosphere had the largest porosity, which was more conducive to gas diffusion. In addition, some of the unreduced Si, Al, Mn, Ca, and Fe in the pellets reduced in the N2 atmosphere will be precipitated in the form of oxides. When the reducing gas (CO, H2) is introduced, no precipitation will occur.